European chronic kidney disease registries for children not on kidney replacement therapy: tools for improving health systems and patient-centred outcomes - Bakkaloğlu, Sevcan A; Vidal, Enrico; Bonthuis, Marjolein; Neto, Gisela; Paripović, Dušan; Åsberg, Anders; Hijosa, Marta Melgosa; Vondrak, Karel; Jankauskiene, Augustina; Roussinov, Dimitar; Awan, Atif; Jager, Kitty J (Clinical kidney journal, 2023)
Chronic kidney disease (CKD) in children, from birth to late adolescence, is a unique and highly challenging condition that requires epidemiological research and large-scale, prospective cohort studies. Since its first launch in 2007, the European Society for Paediatric Nephrology/European Renal Association (ESPN/ERA) Registry has collected data on patients on kidney replacement therapy (KRT). However, slowing the progression of CKD is of particular importance and thus the possibility to extend the current registry dataset to include patients in CKD stages 4-5 should be a priority. A survey was sent to the national representatives within the ESPN/ERA Registry to collect information on whether they are running CKD registries. All the representatives from the 38 European countries involved in the ESPN/ERA Registry participated in the survey. Eight existing CKD registries have been identified. General characteristics of the national registry and detailed data on anthropometry, laboratory tests and medications at baseline and at follow-up were collected. Results provided by this survey are highly promising regarding the establishment of an ESPN CKD registry linked to the ESPN/ERA KRT registry and subsequently linking it to the ERA Registry with the same patient identifier, which would allow us to monitor disease progression in childhood and beyond. It is our belief that through such linkages, gaps in patient follow-up will be eliminated and patient-centred outcomes may be improved.
Keywords: chronic kidney disease; kidney replacement therapy; Europe; registry; children